Measurement of [Omega]0c baryon production and branching-fraction ratio BR([Omega]0c → [Omega]-e+[nu]e)/BR([Omega]0c → [Omega]-π+) in pp collisions at √s =13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Nath, Abhishek; et al. (Physical review, 2024)
The inclusive production of the charm-strange baryon Ω0c is measured for the first time via its semileptonic decay into Ω−⁢e+⁢𝜈e at midrapidity (|𝑦| <0.8) in proton-proton (pp) collisions at the center-of-mass energy √𝑠 =13 TeV with the ALICE detector at the LHC. The transverse momentum (𝑝T) differential cross section multiplied by the branching ratio is presented in the interval 2 <𝑝T <12 GeV/𝑐. The branching-fraction ratio BR⁡(Ω0c →Ω−⁢e+⁢𝜈e)/BR⁡(Ω0c →Ω−⁢𝜋+) is measured to be 1.12 ±0.22 (stat) ±0.27 (syst). Comparisons with other experimental measurements, as well as with theoretical calculations, are presented.
Veröffentlicht: 12. August 2024
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovska, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grundwald, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. Van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [und 1044 weitere Personen]
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Im Titel ist die Zahl 0 sowie die Plus- und Minuszeichen hochgestellt sowie die Buchstaben "c" und "e" tiefgestellt
Gesehen am 01.07.2025